1998
DOI: 10.1111/j.1744-6570.1998.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐other Agreement: Does It Really Matter?

Abstract: A current controversy in the self-other rating and 360-degree feedback literature is the extent to which self-other agreement (and lack of agreement) has an impact on individual and organizational outcomes. Using a large sample and a multi-source data set, the current study addressed some methodological limitations of prior research. Results from polynomial regression analyses demonstrated that both self-and other ratings are related to performance outcomes. This procedure revealed the underlying three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
405
4
10

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(459 citation statements)
references
References 36 publications
40
405
4
10
Order By: Relevance
“…Most research to date has found a lack of agreement between self-ratings and those provided by others (Atwater, Ostroff, Yammarino, & Fleenor, 1998;Johnston & Ferstl, 1999). In addition, discrepancies are usually biased in the direction of self-ratings, i.e., self-evaluations are higher than those by other raters (e.g., Campbell & Lee, 1988;Yammarino & Atwater, 1997).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Most research to date has found a lack of agreement between self-ratings and those provided by others (Atwater, Ostroff, Yammarino, & Fleenor, 1998;Johnston & Ferstl, 1999). In addition, discrepancies are usually biased in the direction of self-ratings, i.e., self-evaluations are higher than those by other raters (e.g., Campbell & Lee, 1988;Yammarino & Atwater, 1997).…”
Section: Background Of the Studymentioning
confidence: 99%
“…The principal investigator conducted telephone interviews and asked the superior to rate the expatriate on the three work adjustment items derived from Black and Stephens (1989). Superior ratings are generally considered a valid alternative to self-ratings in the performance appraisal literature when the supervisor has the opportunity to observe the employee (Atwater, Ostroff, Yammarino, & Fleenor, 1998). A sample item was "Please provide your assessment of the degree of adjustment of an expatriate regarding specific job responsibilities."…”
Section: Methodsmentioning
confidence: 99%
“…Although previous studies have concluded that over-estimators are generally poor performers and less effective (e.g., Atwater et al, 2005;Ostroff et al, 2004;Tekleab et al, 2008;, there are nevertheless some indications that this picture is more nuanced. For example, Atwater et al (1998) found that leaders who received high ratings from others (i.e., peers and subordinates) but provided still higher self-ratings were rated as more effective by their direct supervisor. Likewise, Sosik and Megerian (1999) found that over-estimators received the highest mean performance scores from their superiors as compared with both under-estimators and those in the agreement category.…”
Section: Self-other Agreement and Leader Effectivenessmentioning
confidence: 99%
“…This may prevent them from developing as leaders (Bass & Yammarino, 1991) and lead them to pursue unrealistic tasks that represent risks and uncertainties (Atwater et al, 1998).…”
Section: Self-other Agreement and Leader Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation